Phylogeny of the genus Aulacophora chevrolat (Coleoptera Chrysomelidae: Galerucinae) in sundaland - Barroga, Grace F. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2006)
Phylogenetic analysis of 47 species of Aulacophora Chevrolat in Sundaland based on 59 morphological characters was done using two computer programs - PAUP (Phylogenetic Analysis Using Parsimony) 4.0b6 and MacClade 3.0. The genera Pseudocophora Jacoby and Paridea Baly served as outgroups. Phylogenetic analysis using Pseudocophora as outgroup gave the best resolution of the data set, resulting in 36 most parsimonious trees. Determination of the strict consensus of these trees gave a length of 278+ steps and a consistency index of 0.62. The character of the elytral epipleuron, which is abbreviated distinctly before apex of elytra, unambiguously supports the monophyly of the genus. Characters with high phylogenetic content include: frontal tubercles, orbit (distance between antennal socket and eye), relative eye width, relative length of antennae, antennal segments, anterior margin of pronotum, posterior corners of pronotum, transverse sulcus, punctation of elytra, elytral epipleuron, first tarsal segment, penis, female pygidium, female eighth tergite and female spiculum gastrale. Five species groups were erected based on the analysis, namely, bicolor group, melanocephala group, antennata group, indica group and postica group.